Neurochemical changes in the medial wall of the brain in chronic migraine - Niddam, David M; Lai, Kuan-Lin; Tsai, Shang-Yueh; Lin, Yi-Ru; Chen, Wei-Ta; Fuh, Jong-Ling; Wang, Shuu-Jiun (Brain (London, England : 1878), 2018)
Why do some migraine sufferers progress to the chronic form of the disorder whereas others do not? Niddam et al. show that chronic, but not episodic, migraine is associated with compromised neuronal integrity and distinct reorganization of the thalamocortical pathway. Altered thalamic activity may predispose certain patients to long-term pain. Abstract Migraine chronification is associated with a dysfunctional thalamocortical pathway. The present study addressed whether abnormal concentrations of neurochemicals exist in key brain regions of this pathway in chronic migraine. Magnetic resonance spectroscopic imaging of the bilateral medial walls of the brain was used to measure choline, creatine, glutamate and glutamine, myo-inositol, and N-acetyl-aspartate in chronic migraine patients and in matched groups of episodic migraine patients and healthy controls. A region of interest analysis was conducted to examine whether N-acetyl-aspartate, a marker of neuronal integrity, was reduced in the thalamus, occipital cortex and anterior cingulate cortex in chronic migraine. Interregional N-acetyl-aspartate correlations among these regions of interest were also examined. Additionally, statistical mapping was performed for all the metabolites throughout the medial walls. Chronic migraine was associated with N-acetyl-aspartate reductions in the bilateral thalami and in the right anterior cingulate. The N-acetyl-aspartate reduction in the right thalamus correlated with disease duration. Compared with healthy controls, patients with chronic migraine had altered interregional N-acetyl-aspartate correlations between the right thalamus-anterior cingulate and thalamus-occipital cortex, and between the left and right anterior cingulate. N-acetyl-aspartate concentrations and interregional correlations in patients with episodic migraine were between those of healthy controls and chronic migraine patients. The unconstrained analyses revealed a reduction of myo-inositol in the left anterior and posterior cingulate in both patient groups as well as a negative association with depression scores for the anterior cingulate in the combined patient group. In addition, migraine patients with headache on the scan day (irrespective of diagnosis) had reduced N-acetyl-aspartate and total creatine concentrations in the right dorsal anterior cingulate. Reduced N-acetyl-aspartate metabolism and altered interregional N-acetyl-aspartate correlations lend support to the role of thalamocortical dysfunction in migraine chronification. It remains to be established if the pattern of changes within the N-acetyl-aspartate network is specific to chronic migraine or can be found in other chronic pain conditions.